Visual outcome of ranibizumab therapy for neovascular age related macular degeneration in the black population: a report of five cases - Roopa Vemala (Dove Medical Press, 2010)
Roopa Vemala, Bhaskar Gupta, Sobha SivaprasadLaser and Retinal Research Unit, King’s College Hospital, London SE5 9RS, UKIntroduction: Neovascular age related macular degeneration (AMD) is relatively uncommon in the black population. We report the 12-month outcome of ranibizumab therapy in five black patients with choroidal neovascular membrane (CNV) secondary to AMD.Material and methods: Retrospective analysis of a prospective audit database maintained for all patients on ranibizumab therapy in a retinal specialist unit that caters to a multi-ethnic cohort in London, United Kingdom.Results: At 12 months, all the 5 patients maintained stable vision (loss of less than 15 ETDRS letters). However, none of them gained more than 15 ETDRS letters. All eyes showed early subretinal fibrosis while 2 patients showed extended areas of retinal pigment atrophy.Conclusion: Our case studies indicate that ranibizumab stabilizes the vision in black patients with CNV secondary to AMD but they tend to develop early subretinal fibrosis and retinal pigment atrophy.Keywords: choroidal neovascular membrane, Afro-Caribbean, blacks